Kangkilo Oral Tradition: Reflection of Sufism and Political Powers in Buton Community - Udu, Hamiruddin; Weda Kusuma, I Nyoman; Suarka, I Nyoman; Alifuddin, Muh (e-Journal of Linguistics; Vol 11 No 1 (2017): eJL-JanuaryDO - 10.24843/eJL.2017.v11.i01.p03)
Kangkilo oral tradition is a form of holiness ritual. The values ?? can realize Islamic ritual and social pieties. However, the pursuit of technology results to facilitate the achievement of material according to human needs has made this tradition endangered. This study aimed to analyze the discourse structure, reflection of Sufism and political powers in function and meaning, and also inheritance strategies of kangkilo in Buton community. Data were collected by using an ethnographic approach and analyzed by using qualitative methods. The results showed that the discourse structure, function, and meaning of kangkilo is unique, different from other oral traditions ever observed. The values contained some Sufism understandings and political policies of powers. From the aspect of the formula, for example, although kangkilo is qualified as a form of oral tradition, but actors of kangkilo still expected to follow the text which has been taught, can not to change the text appropriate to the circumstances that exist around kangkilo actors are, as a formula in oral tradition suggested by experts such as Albert B. Lord. This is related to the presence of kangkilo as a religious ritual. Kangkilo oral tradition is a ritual holiness in Buton influenced by Sufism understanding in MartabatTujuh. By the influence of Sufism in kangkilo , have made this holiness ritual different with the other ritual of purity which is known in the Islamic world. Kangkilo is used also as a marker for people who live in Buton as Butonese. The values in kangkilo are used as values standard for social and cultural development in Buton community. From the aspect of meaning, chastity teachings both theocentric and anthropocentric in kangkilo oral tradition values led the creation of a harmonious of life, both in man's relationship with God, between one people and other people, as well as between the rulers and the people, and between people and nature universe. Given the importance of these rituals for human life, especially the Buton, kangkilo the oral tradition is expected to continue to be studied and implemented. Therefore, in order to revive kangkilo oral tradition, inheritance need to adopt a system of formal education learning and use the modern media.
Keywords: Oral tradition, kangkilo, Butoncommunity